Dos enemigos naturales de Tydeus californicus y Lorryia formosa - Cabrera, R.I.
(Es, En)
Ilus., ref.
Keywords: CITRUS SINENSIS; PLAGAS DE PLANTAS; ACARINA; TYDEIDAEHONGOS; HIRSUTELLA; ENEMIGOS NATURALES; AGENTES DE CONTROL BIOLOGICO; PLAGAS; CUBA